Adaptation And Validation Of An Arabic Version Of Multiple Intelligence Development Assessment Scale (midas) And The Relationship Between Two Modes Of Midas Assessment - Mohmmad Al-Sabbah, Saher Ali (2009)
Tujuan kajian ini adalah untuk mengadaptasi dan mengesahkan skala MIDAS kepada versi bahasa Arab